Simulating Nucleic Acid Oxidation Using Electrochemistry/Liquid Chromatography/Mass Spectrometry - Oberacher, H. (Association of Biomolecular Resource Facilities, 2010)
RP-62 Reactive Oxygen Species (ROS) are a result of normal metabolism processes but in contact with toxic factor radiation or carcinogenic substance can cause nucleic acids modification and lead to DNA damage. Additionally, some drugs may form covalent bonds with nucleic acids resulting in such modifications. The DNA repair enzymes are monitoring the alterations, but unless errors are not fixed cell death, malignancy and aging may occur. Combining on-line electrochemistry (EC) with electrospray mass spectrometry (EC/ESI-MS) provides a powerful tool for simulating multiple oxidation processes, and among others oxidation of nucleic acids. ESI-MS allow directly monitoring of the reaction products and elucidating their structures by means of fragmentation experiment (MS/MS). In this poster we present the application of on-line EC/ESI-MS to study oxidative processes involving nucleic acids. It is demonstrated that EC is a useful tool for the activation of drug compounds to form covalent adducts with nucleic acids. EC/ESI-MS can be used for large-scale studies on the impact of sequence, structure, and modifications on nucleic acid oxidation as well as for assessing the risk of adduct formation between nucleic acids and chemicals. Moreover, on-line coupling of EC with liquid chromatography (LC) and MS, i.e., EC/LC/MS, is presented. Mass voltammograms containing valuable quantitative information about all major components were measured successfully. Ion suppression effects, which are usually observed in on-line EC/MS and which can severely hamper quantitative experiments, are excluded or at least reduced via chromatographic separation prior to mass spectrometric detection. In addition, on-line EC/LC/MS allowed identification of two different guanosine dimers after conjugation with acetaminophen (APAP).